Grain size effect on interfacial segregation in nanomaterials. (May 2022) - Danoix, F.; Hoummada, K.; Maugis, P.; Rolland, N.; Debreux, C.; Blavette, D.
Abstract: Segregation of impurities to grain boundaries in materials impact their structural, mechanical, electrical or functional properties. In the present paper, a theoretical study of the influence of grain size on grain boundaries segregation in a binary system by coupling the McLean theory, the concept of excess number with the grain boundaries fraction, is presented. The obtained results show that both grain boundary and bulk solute content decrease with reducing the grain size. However, it is shown the equilibrium segregation rate to grain boundaries increases. This effect is enhanced when the grain size is lower than 10 μm and thus should be amplified in nanomaterials. This size dependence is larger at low temperatures, where segregation becomes more pronounced. Highlights: Development of a numerical approach for quantifying equilibrium interfacial segregation. Comparative evolution of solute contents at grain boundaries and bulk. Investigation of the influence of the grain size on the interfacial solute segregation and on the equilibrium segregation rate. Possibility of measuring equilibrium interfacial segregation through bulk composition measurement for small grain structures.